1999
DOI: 10.1002/(sici)1521-4125(199905)22:5<443::aid-ceat443>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Batch Drying in an Inert Medium Fluidized Bed

Abstract: A modified three-phase model is proposed for batch drying of fine powders in an inert medium fluidized bed. The overall heat and mass transfer coefficients between the interstitial gas and solid phases have been determined by the proposed surfacestripping model in which the Biot number is a governing parameter. The effects of gas velocity, inlet gas temperature and mass ratio of starch to inert particles on the drying characteristics of starch in a 0.083 m ID´0.80 m high medium fluidized bed have been determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Lee and Kim [6,7] investigated the effects of gas velocity, inlet gas temperature and the mass ratio of starch to inert particles on the drying rate of starch in an inert medium fluidized bed. They concluded that the drying rate in an inert medium fluidized bed increased with increasing inlet gas temperature and velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Kim [6,7] investigated the effects of gas velocity, inlet gas temperature and the mass ratio of starch to inert particles on the drying rate of starch in an inert medium fluidized bed. They concluded that the drying rate in an inert medium fluidized bed increased with increasing inlet gas temperature and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Solid temperature curve for various glass inerts, 60 C, 0.500 kg inert, 2.36 m/s air velocity (Exp 7,8,11,12)…”
mentioning
confidence: 99%
“…In the above equations, it should be taken into account that: [28] Re t ¼ Ar 18 þ 0:6 ffiffiffiffiffi ffi Ar p ð15Þ…”
Section: Overall Mass and Heat Transfer Coefficientsmentioning
confidence: 99%
“…[28] The basic physicochemical properties of these materials are summarized in Table 1. [28] The basic physicochemical properties of these materials are summarized in Table 1.…”
Section: Batch Drying Kinetics 1623mentioning
confidence: 99%
See 1 more Smart Citation